Cancer-specific mortality in patients with non-metastatic renal cell carcinoma who have undergone a nephrectomy and are eligible for adjuvant pembrolizumab - Flammia, Rocco S; Hoeh, Benedikt; Hohenhorst, Lukas; Sorce, Gabriele; Chierigo, Francesco; Panunzio, Andrea; Tian, Zhe; Saad, Fred; Leonardo, Costantino; Briganti, Alberto; Antonelli, Alessandro; Terrone, Carlo; et al. (Seminars in oncology, 2022)
BACKGROUND: Data in patients with malignant melanoma, who have been previously treated with pembrolizumab as adjuvant therapy, show a reduction in pembrolizumab efficacy upon rechallenge. We examined this scenario in patients with non-metastatic renal cell carcinoma (RCC) eligible for adjuvant pembrolizumab after nephrectomy. We hypothesized that a proportion of such patients will either require re-treatment with pembrolizumab upon metastatic progression prior to cancer-specific mortality (CSM) or die from other cause mortality (OCM). MATERIALS AND METHODS: We identified within the SEER database 10,635 patients, between 2004 and 2017, with a diagnosis of non-metastatic intermediate-high and high risk RCC, who had undergone nephrectomy and fulfilled criteria for enrollment in KEYNOTE-564. Kaplan-Meier analyses addressed overall survival (OS), CSM and OCM. RESULTS: 9,825 (92.4%) of the 10,635 patients had intermediate-high risk RCC and 9,456 (88.9%) underwent radical nephrectomy. Additionally, 760 (7.1%) harbored sarcomatoid features. In Kaplan-Meier analyses, median OS was 9.8 (9.1-11.4) years. At 10-years of follow-up, CSM rate was 36% and OCM rate was 22%. CONCLUSIONS: Based on CSM, our observations indicate that by 10-years of follow-up 36% of patients treated with adjuvant pembrolizumab will require a rechallenge, in a setting where a checkpoint inhibitor may have reduced efficacy. Moreover, at 10-years of follow-up, 22% of patients with RCC, previously treated with adjuvant pembrolizumab, will die of other causes. These percentages should be strongly considered prior to routine use of adjuvant pembrolizumab, especially given an OS benefit has not been proven.
Keywords: karcinom z renálních buněk; humanizované monoklonální protilátky; nádory ledvin; SEER Program; lidé; program SEER; Antibodies, Monoclonal, Humanized; nefrektomie; Humans; Carcinoma, Renal Cell; Kidney Neoplasms; Nephrectomy